Development of Project Based Learning With STEAM Approach Model in Improving the Science Literacy Ability of High School Students - Nuraini Nuraini*; Nurul Fajri; Indra Himayatul Asri; Edy Waluyo (Universitas Syiah Kuala, 2023)
Facing today's 21st century learning, teachers need to foster science literacy and consider learning strategies that are appropriate to the conditions and potential of learners. This study aims to develop a PjBL with STEAM approach model in improving science literacy ability of high school students. This study is a development research with the Borg Gall development model. The sample of this study was class X students of SMAN 2 Selong, totaling 35 students. The instruments used to collect data include guidelines for validating learning design, practicality questionnaires and science literacy ability tests on ecosystem materials. The data analysis used in this study used descriptive analysis. Based on the validation analysis, the products developed are included in the valid category indicated by the average score of product validation by 3 experts, namely linguists, material experts and learning technology experts successively 83.91; 84.64 and 83.73. Similarly, in terms of practicality, the products developed are also classified as practical with an average practicality score of 82.63. The product is also classified as effective with a percentage of effectiveness of 88.57%. The product developed has a potential effect in the high category to improve science literacy ability on ecosystem materials with an N-Gain of 0.76